A novel homozygous intronic variant in CDT1 that alters splicing causes Meier–Gorlin syndrome, and a review of published mutations and growth hormone treatments - Qing Li; Yichi Wu; Fucheng Meng; Zhuxi Li; Di Zhan; Xiaoping Luo (Orphanet Journal of Rare Diseases)
Abstract Background Meier–Gorlin syndrome (MGORS) is a rare autosomal inherited form of primordial dwarfism. Pathogenic variants in 13 genes involved in DNA replication initiation have been identified in this disease, but homozygous intronic variants have never been reported. Additionally, whether growth hormone (GH) treatment can increase the height of children with MGORS is unclear. Methods The medical history data of a young girl were collected and reviewed. Whole-exome sequencing (WES) and bioinformatic analysis were performed to identify any variants and predict their pathogenicity. Minigene constructs were generated and transfected into HEK-293T cells for in vitro splicing assays. The literature was reviewed to explore the mutational spectrum and efficacy of GH treatment for this disease. Results A girl with microtia, hypoplastic patellae, and severe growth retardation carried a novel homozygous intronic variant (NM_030928.4: exon 3: c.352–30 A > C) in CDT1. The variant was predicted to break a branch point and alter splicing, and the minigene assay confirmed abnormal splicing with exon 3 skipping. The patient was treated with GH for 5 years, with an increase in growth velocity from 4.0 cm/year to an average of 6.2 cm/year. A literature review revealed that the most common variant type and inheritance state were missense and compound heterozygous, respectively. Additionally, the vast majority of children with MGORS treated with GH had normal insulin-like growth factor 1 (IGF-1) levels, and half of them responded positively to GH therapy. Conclusions We reported a novel pathogenic homozygous intronic variant (c.352–30 A > C) of CDT1 in a girl with MGORS, and this mutation extended the genetic spectrum of the disease. GH therapy may be beneficial for height outcomes in children with MGORS with normal IGF-1 levels.